Kemampuan Menulis Teks Deskripsi Siswa Kelas VII SMPN 20 Kupang - Lende, Margaretha Aryani; Margareta, Karus; Leda, Anastasia (Jurnal Lazuardi, 2025)
The focus of this study is “the ability to write descriptive text of grade VII students of SMPN 20 Kupang”. The theory used is the theory of writing, because what is measured in this study is the ability of students to write descriptive text with the ability of students to observe an object. The method used in this study is qualitative descriptive. In this study, the researcher chose material about descriptive text by developing KD 4.2 presenting data, ideas, impressions in the form of descriptive text about objects (schools, tourist attractions, historical places, and/or regional arts performance atmosphere) in writing and orally by paying attention to the structure both orally and in writing. Descriptive text requires students to describe in detail an object or situation, which helps assess their ability in using vocabulary, grammar, and the ability to convey information correctly. Based on the results of the analysis conducted on 25 students of class VII-A SMPN 20 Kupang, the ability to write descriptive text by paying attention to the structure of the descriptive text can be said to be successful because, there were 17 students who completed with a percentage of 68% and 8 students did not complete with a percentage of 32%.